OPTIMALISASI TATA KELOLA KEARSIPAN - Eka Setiyawati (JENTRE, 2020)
This study aims to determine how is archives management by utilizing makeshift facilities and infrastructure around us in supporting administrative services at the Ministry of Religion Office Jambi City. This research uses descriptive method with qualitative data. Observations include the implementation of archive management process, and the role of planning, organizing, monitoring and paying attention to the factors that determine archive management cover human resources, infrastructure, budget, support and leadership attention. The data analyzed were the results of observations and interviews with the Head, Sub. Administration Section, Section Head, Coordinator, and Staffs in the Office. The results showed that archives management although only supported by minimal facilities and infrastructure, still refers to archival management patterns of classification, guidelines for handling letters and structuring files. The results also show that the management is in accordance with archival standards, but the facilities and infrastructure used have not met archiving standards. A very determining factor for the success of archives management in supporting administrative services is the support from the leader and the budget. Without it, archive management activities cannot run optimally. In addition to budget, the need for facilities infrastructure may not be fulfilled.